The valkyries : an encounter with angels - Coelho, Paulo, 1947- (HarperTorch, 2004)
This is a modern-day adventure story featuring Paulo’s supernatural encounter with angels – who appear as warrior women and travel through the Mojave desert on their motorbikes.